2006
DOI: 10.1111/j.1467-8578.2006.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Until somebody hears me: parent voice and advocacy in special educational decision making

Abstract: When a family finds out their child has a disability, they enter the world of special education which has its own terminology, rules, settings, and personnel. In addition to grappling with the meaning of their child's special needs, families are also thrown into the role of principle advocate for their child. This research study presents the findings from focus groups conducted with 27 diverse families on their efforts to obtain the best educational outcomes for their children. In this article, Robyn Hess, Eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 19 publications
7
92
2
2
Order By: Relevance
“…In the following sections, the seven analysis techniques are presented, along with guidelines for utilizing NVivo software for each type of analysis. Finally, real data from Hess, Molina, and Kozleski (2006) have been analyzed and screenshots of what would appear with NVivo8 are included.…”
Section: Descriptions and Computer Guides Of A Variety Of The Availabmentioning
confidence: 99%
“…In the following sections, the seven analysis techniques are presented, along with guidelines for utilizing NVivo software for each type of analysis. Finally, real data from Hess, Molina, and Kozleski (2006) have been analyzed and screenshots of what would appear with NVivo8 are included.…”
Section: Descriptions and Computer Guides Of A Variety Of The Availabmentioning
confidence: 99%
“…For example, research has demonstrated instances in which it is not typical practice for school personnel to invite parents to discuss issues related to IEP development (Duquette, Fullarton, Orders, Robertson-Grewal, 2011). Relatedly, special education teachers prepare IEPs in isolation and prior to IEP meetings according to the required information for each section as set by the state procedures for doing so (Hess et al, 2006). Therefore, once the IEP meeting occurs, there is very little opportunity for generating new ideas on the basis of parental input.…”
Section: Idea and Family Involvementmentioning
confidence: 99%
“…The partnership between the family of a student with disabilities and a school is very important in the special education process because a supportive family structure contributes positively to the education and progress of students with disabilities (Hess, Molina & Kozleski, 2006). Families, and specifically parents, know their child's needs best and are therefore positioned to assert their child's interests and make decisions as to what is educationally appropriate for him or her (Lo, 2010).…”
Section: Idea and Family Involvementmentioning
confidence: 99%
See 2 more Smart Citations